Question #ae8df

1 Answer
Mar 23, 2017

x={0,pi/4,3/4pi,pi,5/4pi,7/4pi,2pi}x={0,π4,34π,π,54π,74π,2π}

Explanation:

tan^8 x -tan^4 x=tan^4x(tan^4x-1)=0tan8xtan4x=tan4x(tan4x1)=0

so we have

tan^4 x=0->tan x = 0tan4x=0tanx=0

and

tan^4x-1=(tan^2x+1)(tan^2x-1)=(tan^2x+1)(tanx-1)(tanx+1)tan4x1=(tan2x+1)(tan2x1)=(tan2x+1)(tanx1)(tanx+1)

Here tan^2x+1=0tan2x+1=0 is unfeasible so we will consider only

{(tanx=0),(tanx=1),(tanx=-1):}

and then

x = kpi uu x=pi/4+kpiuux=3/4pi+kpi for k=0,1,2,cdots

or

x={0,pi/4,3/4pi,pi,5/4pi,7/4pi,2pi}